A new identity-based ring signcryption scheme. (17th November 2014) - Deng, Lunzhi; Zeng, Jiwen; Li, Siwei
This paper presents a new identity-based ring signcryption scheme. With this technique, anyone can choose n – 1 entities to generate a verifiable ring signcryption on behalf of the group of n members, yet the actual signcrypter remain anonymous. The scheme is proven to be indistinguishable against adaptive chosen ciphertext attacks, existentially unforgeable against adaptive chosen message and identity attacks, and unconditional signcrypter ambiguity under the random oracle model.